Determining of the water quality of the ping river at different seasons in northern Thailand - Fumihiko Ogata (2020)
© 2020 Pharmaceutical Society of Japan. All rights reserved. The water quality in a river (water environment) is very important for human health and aquatic organisms. In 2015, the highly regarded Water Resources Management Strategy of Thailand was announced by The Ministry of Industry in Thailand. In this study, the water quality of the Ping river in Northern Thailand, including Chiang Mai and Lamphun provinces, was focused on and measured for three different seasons (summer, rainy, and winter seasons). Anions (F-, Cl-, NO2-, NO3-,and SO42-) and cations (Na+, Mg2+, Si4+, S6+, K+, and Ca2+) were qualified by an ion chromatograph and an inductively coupled plasma optical emission spectrometry, respectively. The concentration of anions and cations (except for Mg2+and Ca2+) in the Ping river at upstream (countryside) locations were lower than that at downstream (closer main city) locations, which indicated that the fertilizers, industrial or household wastewaters had been flowing into the Ping river at downstream locations. Additionally, the concentration of anions and cations in the rainy season was higher than other seasons. The present results provide the water quality of the Ping river which was not yet reported officially by the Thailand government.